Ketidakadilan dalam Informasi Kriminal (Wacana Pembandingan Aktor Berita Kriminal di Headline Surat Kabar Koran Merapi) - Anwar Riksono Dian Nugroho (Jurnal Ilmu Komunikasi, 2013)
Abstract: Headline, the main news in the front of page of a newspaper, is a strategic place to convey information. Of course, headline in yellow journalism ought to be attractive with bombastic content’s characteristic and sometimes it shows off sensuality. Koran Merapi is one of newspaper which has the positioning as a law and criminal newspaper. In other side, Criminal reality always shows some characters such as: suspect, police and victim. Based on constructivism ideas, mass media will always construct reality to be published in media. It means that reality in media will re-construct those characters. The research question is formulated as follows: how is the criminal actor constructed by Koran Merapi? Using critical approach through discourse analysis, the research will investigate the basic idea of occurring construction. Van Leeuwen’s models for the text analysis and Norman Fairclough’s for the context are used to explore actor and marginalization in criminal news. The police are depicted as somebody who is admirable and acts as the superhero. The suspects are depicted as a strong person before the victim but weak before the police. The victims are the characters who are always threatened by crimes, are not able to overcome it without any help from the hero.